Multilingual Education From Students: Case Study in Israel and Moldova - Wittman, Hana (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: This study sets out on an innovative exploration to understand the nuanced learning needs of students, particularly focusing on the often-neglected areas of non-formal and multilingual education. Methodology: Utilizing a robust quantitative survey methodology, this research draws insights from a carefully designed questionnaire comprising 20 rigorously validated statements, achieving a commendable Cronbach's alpha reliability coefficient of 0.82. The study centers on a diverse group of 200 secondary school students from the culturally diverse landscapes of Israel and Moldova. Main Findings: The study investigates the external influences of national and institutional education policies, as well as transformative educational reform initiatives. Internally, it explores personal aspirations such as the desire for knowledge enhancement, professional retraining, and pursuit of individual interests and leisure activities. Furthermore, the research delves into the complex role of foreign languages in the educational framework, highlighting significant gaps in teacher proficiency, pedagogical methodologies, contemporary learning resources, and assessment practices. Novelty/Originality of this study: The uniqueness of this study lies in its recognition of the multifaceted benefits of multilingual education, which goes beyond cognitive development to foster emotional and social enrichment. Central to this discussion is the concept of interlanguage transfer, a phenomenon that captures the dynamic interaction between the languages of bilingual or multilingual individuals, significantly influencing their linguistic abilities. This study not only emphasizes the importance of multilingualism in educational settings but also highlights its potential to enhance the educational experience for students, educators, and society as a whole.